تحقيق المناط وضوابط إعماله في باب المعاملات المالية المعاصرة - بدادي, بوكة (جامعة الوادي University of Eloued, 2015)
يتطرق موضوع البحث إلى حقيقة تحقيق المناط، كما يبين أثر تحقيق المناط في ضوء مقاصد الشريعة في ضبط المعاملات المالية المعاصرة، وتخلص الدراسة إلى أهمية توظيف تحقيق المناط في العمل الاجتهادي المعاصر، وكذا مدى إمكانية ضبط الاجتهادات الفقهية المعاصرة واختبار مدى صحتها. ABSTRACT: This research deals with the concept of establishment of " Manat ", and it indicates the impact of establishment of " Manat "in the light of the purposes of Sharia to adjust contemporary financial transactions, this study includes the importance of establishment of " Manat " in contemporary jurisprudence, and the possibility of adjusting the contemporary jurisprudence and test their veracity.
Establishment Of " Manat " And The Controls Of Its Enforcement In Contemporary Financial Transactions
Keywords: تحقيق المناط، التعليل، المعاملات المالية، الضوابط